Wind tunnel testing of a ducted-fan unmanned aerial vehicle - Shiah, Zi Yang. (2011)
This report has investigated the effects of the aerodynamic parameters of lift, drag, moments and thrust and determined their relationships with different wingspans at different pitch and wing incidence angles on a ducted-fan Micro Air Vehicle (MAV) at a speed of approximately 15m/s. The experiments were carried out in a closed-loop wind tunnel with the full-scale MAV at different configurations.